2018
DOI: 10.1002/jcb.27257
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: Long noncoding RNA SNHG16 contributes to the development of bladder cancer via regulating miR‐98/STAT3/Wnt/β‐catenin pathway axis

Abstract: This study aimed to investigate the role and the possible mechanism of the long noncoding small nucleolar RNA host gene 16 (SNHG16) in bladder cancer development. The expression of SNHG16 in the tumor tissues and plasma of patients with bladder cancer as well as bladder cancer cell lines was detected. T24 cells were then transfected with sh-SNHG16 to further investigate the effects of suppression of SNHG16 on T24 cell proliferation, apoptosis, migration, and invasion. In addition, the regulatory relationships … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(57 citation statements)
references
References 36 publications
1
56
0
Order By: Relevance
“…lncRNA SNHG16 was showed to be regulated by the wnt pathway in colorectal cancer [40]. Additionally, SNHG16 has also been reported to associate with many other cancers, such as bladder cancer and pediatric neuroblastoma [41,42]. As of now, the remaining lncRNAs (AP006621.2, AL354993.2, AC048344.4, GS1-124K5.4, AC010973, AL590483.1, AL137782.1, STAG3L5P-PVRIG2P-PILRB, and AP001554.1) are rarely reported in the previous studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…lncRNA SNHG16 was showed to be regulated by the wnt pathway in colorectal cancer [40]. Additionally, SNHG16 has also been reported to associate with many other cancers, such as bladder cancer and pediatric neuroblastoma [41,42]. As of now, the remaining lncRNAs (AP006621.2, AL354993.2, AC048344.4, GS1-124K5.4, AC010973, AL590483.1, AL137782.1, STAG3L5P-PVRIG2P-PILRB, and AP001554.1) are rarely reported in the previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…lncRNAs dominate the upstream portion of the RNA network and function as primary effectors of mRNAs, and several lncRNAs are identi ed as potential prognostic factors in COAD [20,30]. Among these 14 lncRNAs in the model, PCAT6, CASC9, MIR4435-2HG, SNHG16, and LINC00513 have been reported to play a role in the pathogenesis and prognosis of various cancer types (31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43). For example, CASC9 has been reported to be upregulated and conferred an oncogenic function in human hepatocellular carcinoma, oral carcinoma, gastric cancer, colorectal cancer, and esophageal cancer [28,[31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…They further stated that SNHG16 could sponge miR-98 and target STAT3 through the Wnt/ β-catenin pathway to act as an oncogene in bladder cancer. 55 And SNHG16 acts as a ceRNA in colorectal cancer cells to suppress miR-200a-3p and increase the expression of ZEB1 and, thereby, promote the expression of EMT-related genes, such as cadherins and vimentin, and promote cell migration and invasion. Similarly, Zhu et al revealed that silencing SNHG16 inhibits cell migration and invasion, and EMT in vitro, indicating that SNHG16 is involved in the tumorigenesis of cervical cancer (CC).…”
Section: Activating Migration and Invasionmentioning
confidence: 99%
“…to date, the lncRNA small nucleolar RNA host gene 16 (SNHG16) has been well-documented in several types of cancers including bladder cancer, liver cancer, cervical cancer, glioma and osteosarcoma. [15][16][17][18] However, the role of SNHG16 in CVDs has not been explored yet.…”
Section: Upmentioning
confidence: 99%
“…The lncRNA myosin heavy‐chain‐associated RNA transcripts were found to protect the heart from pathological hypertrophy . Up to date, the lncRNA small nucleolar RNA host gene 16 (SNHG16) has been well‐documented in several types of cancers including bladder cancer, liver cancer, cervical cancer, glioma and osteosarcoma . However, the role of SNHG16 in CVDs has not been explored yet.…”
Section: Introductionmentioning
confidence: 99%